МЕТОДИЧНИЙ ПІДХІД ДО ЕКОНОМІЧНОЇ ОЦІНКИ ТЕХНОЛОГІЧНИХ ІННОВАЦІЙ - Dolyna, I.V. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2007)
Proposals on establishment of the prices for technological innovations under conditions of full and incomplete transfer of the rights to them to the consumer are made. The basis of the offered technique is definition of upper arid bottom lines in possible interval of marketing field of price policy. Recommendations on establishment of the actual price take into account interests of both the developer, and the consumer of a technological innovation to able greatest extent. A special attention is given to questions of pricing under incomplete transfer of rights to use technological innovations to the consumer.